Role of E-Media in Public Policy Awareness: A Study on Majuli River Island, Assam - Dr. Md. Mofidur Rahman (International Journal of Advanced Science and Technology, 2020)
Public policy is the backbone of any welfare sates. The government formulates various schemes and policies so as to elevate the socio-economic status of the people. However, it’s noteworthy that people live in the periphery is not aware of various government policies, and schemes. As a result, they are not getting the policy benefits. On the other hand with the adoption of the New Economic Policy (NEP), 1991 Indian economy was liberalised which resulted in a huge transformation in the electronic media sector. This radical change in the media sector changed many aspects of our daily life. Television has become a household commodity for everyone and people spend viewing them increased dramatically. In this paper, an attempt has been made to understand the relationship between electronic media and the level of policy awareness. The main theoretical argument of this paper is that electronic media has a direct effect on citizen’s political knowledge. The higher level of access to electronic media enhances the level of policy awareness and citizen’s knowledge of public affairs, governance, and a sense of government efficacy. Hence, the main objective of this paper is to understand the relationship between electronic media and level of policy awareness in Majuli, the largest inhabited river island of the world.